2020
DOI: 10.3897/zookeys.1008.54190
|View full text |Cite
|
Sign up to set email alerts
|

Caridina sinanensis, a new species of stygobiotic atyid shrimp (Decapoda, Caridea, Atyidae) from a karst cave in the Guizhou Province, southwestern China

Abstract: From a biodiversity survey of a subterranean habitat near Sinan County, Guizhou Province, southwestern China, a new atyid shrimp of the genus Caridina H. Milne Edwards, 1837, C. sinanensissp. nov. was discovered. The new species can be separated from other congeners based on a combination of characters including depigmentation in body and reduction of eyes, small pigment spot at the centre of the cornea, the shape of rostrum and the endopod of the 1st male pleopod, and the relatively longer appendix interna on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Reduced eyes Caridina (with cornea pigmentation ranging from totally absent to a small black spot) and blind Gammarus are known by many narrowly distributed species from several caves in south China [46][47][48], mostly described in recent years. Their presence in Feihu Dong is in line with this distribution.…”
Section: Discussion On Some Animals Found In Cave Feihu Dongmentioning
confidence: 99%
“…Reduced eyes Caridina (with cornea pigmentation ranging from totally absent to a small black spot) and blind Gammarus are known by many narrowly distributed species from several caves in south China [46][47][48], mostly described in recent years. Their presence in Feihu Dong is in line with this distribution.…”
Section: Discussion On Some Animals Found In Cave Feihu Dongmentioning
confidence: 99%
“…Cai & Ng (2018) reported a new cave-dwelling atyid Caridina jiangkou from Jiangkou County, which is also of the typical epigean form. More recently, Xu et al (2020) reported Caridina sinanensis from Sinan County, which is unpigmented, and the cornea is vestigial with only a small pigment spot.…”
Section: Introductionmentioning
confidence: 99%